Identifikasi Carmovirus pada Tanaman Anyelir melalui Teknik Reverse Transcription-Polymerase Chain Reaction dan Analisis Sikuen Nukleotida - Rizki Haerunisa; Erniawati Diningsih; Gede Suastika (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Mottle disease of carnation (Dianthus caryophyllus) was observed in cultivation areas in Cianjur and Bandung, West Java. This study aimed to identify the virus causing leaf mottling on carnation using reverse transcription-polymerase chain reaction (RT-PCR) method and nucleotide sequence analysis. Fragment DNA of 1000 bp was successfully amplified using specific primers for coat protein of Carmovirus (BC57/BC58). Direct sequencing was proceeded using PCR products. Nucleotide sequence analysis confirmed the infection of Carnation mottle virus (CarMV) from leaves showing mottle symptom. Furthermore, phylogenetic analysis showed that CarMV isolates from Indonesia have close relationship with those from Brazil, Israel, Iran, India, Netherland, and Spain.